Extreme ultraviolet time-resolved photoelectron spectroscopy of aqueous aniline solution: enhanced surface concentration and pump-induced space charge effect. (17th January 2021) - West, Christopher W.; Nishitani, Junichi; Higashimura, Chika; Suzuki, Toshinori
Abstract : We present extreme ultraviolet (XUV) time-resolved photoelectron spectroscopy (TRPES) of an aqueous aniline solution. One-colour XUV-induced photoemission signal of aniline was observed with much greater intensity than expected from its molar fraction in the bulk solution, indicating that aniline is hydrophobically segregated on the liquid surface. The concentration dependence of the photoelectron intensity is found to be well correlated with the surface concentration of aniline estimated by surface tension measurements. Similar segregation was observed also for phenol in aqueous solution. The enhanced surface concentration of aniline makes its XUV-TRPES to be highly vulnerable to the pump-induced space charge effects (PISC). The PISC caused by a moderate pump intensity was not completely corrected using a simple mean field model, and reduction of the pump pulse intensity was necessary. The spectra measured at lower pump intensity were corrected for PISC, which enabled us to extract the information on the excited state dynamics of aniline in aqueous solution under 240 nm photoexcitation. Two components with lifetime on sub-ps and >100 ps timescales were determined, and the former is ascribed to the solvation dynamics in the S 1 state after the ultrafast internal conversion from the S 3 state and the latter to the subsequent population decay of the S 1 state. GRAPHICAL ABSTRACT: